The standard deviation of life-length, retirement incentives, and optimal pension design - Thomas Aronsson; Sören Blomquist (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper, we consider how the retirement age as well as a tax financed pension system ought to respond to a change in the standard deviation of the length of life. In a first best framework, where a benevolent government exercises perfect control over the individuals' labor supply and retirement-decisions, the results show that a decrease in the standard deviation of life-length leads to an increase in the optimal retirement age and vice versa, if the preferences for 'the number of years spent in retirement' are characterized by constant or decreasing absolute risk aversion. A similar result follows in a second best setting, where the government raises revenue via a proportional tax (or pension fee) to finance a lump-sum benefit per year spent in retirement. We consider two versions of this model, one with a mandatory retirement age decided upon by the government and the other where the retirement age is a private decision-variable.
Keywords: D61; D80; H21; H55; 330; uncertain lifetime; retirement; pension system; Gesetzliche Rentenversicherung; Altersgrenze; Sterblichkeit; Flexible Altersgrenze; Optimale Besteuerung; Risikoaversion; Theorie